Projection of Japan's Population 2022-2052 - Novytskyi, Volodymyr; Miskolczi, Martina; Hon, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis presents a comprehensive projection of Japan’s population from 2020 to 2050, focusing on the country’s well-documented demographic transformation: rapid population aging, persistent low fertility, and sustained population decline. Employing the cohort-component method, the analysis integrates dynamic assumptions for fertility and mortality alongside a fixed migration scenario, drawing on the most recent data from Japan’s national statistical sources and international demographic databases. Future total fertility rate (TFR) projections are developed using ARIMA time series and Bayesian hierarchical models. The study finds that Japan’s population is set to decline sharply—from approximately 126 million in 2020 to just above 102 million by 2050—while the proportion of elderly (65+) will surpass 35%. The analysis confirms the robustness of the applied methodology, as results closely track official projections from the National Institute of Population and Social Security Research (IPSS). Shifts in the age structure will intensify demographic pressures on the workforce and welfare systems, highlighting Japan’s position as a leading example of challenges that other developed societies will soon face. Beyond population numbers, the thesis discusses the broader implications of demographic change for policy and society. It concludes that mitigating the effects of population decline and aging will require integrated responses across family policy, labor markets, migration, and social support for the elderly. The findings offer evidence-based insights relevant to policymakers and researchers and contribute to ongoing debates on demographic sustainability in aging societies.
Vedoucí práce: Martina Miskolczi
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses